2016
DOI: 10.4236/ajac.2016.79060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Some Important Forage Quality Attributes of Southeastern Wildrye (<i>Elymus glabriflorus</i>) Using Near-Infrared Reflectance Spectroscopy

Abstract: Southeastern wildrye (Elymus glabriflorus, Vasey ex L.H. Dewey) is a cool-season, perennial grass native to southeastern United States. Recently, there is a growing interest in its development as a grazing and haying forage crop due to its wide area of adaptation across this region. Consequently, there is a great need for the evaluation of its forage quality by rapid, but accurate analytical methods like Near-Infrared Reflectance Spectroscopy (NIRS). In this study, acceptable NIRS calibration models were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
4
19
1
Order By: Relevance
“…The SWIR region is also widely used for CP and NDF estimation in forage [6,7,13,29,76,78,[92][93][94][95][96][97][98]. Our results are in agreement with other studies that have also reported the importance of the SWIR region, and specifically for the wavelengths of 2202 nm (CP in rapeseed, R 2 = 0.98 [99] and 2204 nm (NDF in forage, R 2 = 0.97 [16].…”
Section: Discussionsupporting
confidence: 90%
“…The SWIR region is also widely used for CP and NDF estimation in forage [6,7,13,29,76,78,[92][93][94][95][96][97][98]. Our results are in agreement with other studies that have also reported the importance of the SWIR region, and specifically for the wavelengths of 2202 nm (CP in rapeseed, R 2 = 0.98 [99] and 2204 nm (NDF in forage, R 2 = 0.97 [16].…”
Section: Discussionsupporting
confidence: 90%
“…For developing and validating the calibration models in the present study, we used the basic methods described in detail earlier by Saha et al . and Rushing et al . The important differences of the present study compared to the earlier studies are adequately described below, allowing an opportunity to follow the protocol for future studies (if needed).…”
Section: Methodsmentioning
confidence: 99%
“…However, this study has some important differences with the earlier study [31] as described and discussed adequately hereunder paying due attention to be brief but giving the full opportunity to the other researchers to follow the protocol for their future studies (if needed).…”
Section: Development and Validation Of Calibration Modelsmentioning
confidence: 86%
“…The basic protocols used to develop and validate the calibration models in this study have been elaborately described earlier by Rushing et al [31]. However, this study has some important differences with the earlier study [31] as described and discussed adequately hereunder paying due attention to be brief but giving the full opportunity to the other researchers to follow the protocol for their future studies (if needed).…”
Section: Development and Validation Of Calibration Modelsmentioning
confidence: 99%